2009
DOI: 10.1063/1.3179808
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal collisionless power absorption using effective viscosity model in inductively coupled plasma discharges

Abstract: Effective viscosity model for inductively coupled plasma (ICP) discharges has been used to calculate the power absorbed inside ICP discharges. It is found that it can be used to calculate collisionless heating, which is a warm plasma effect. The validity of effective viscosity model has been checked by comparing it with kinetic model for warm ICP discharges. For very small plasma lengths, the results of both models are the same. At intermediate lengths where bounce resonance heating is important, results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…10,11 This model has been used recently to calculate the nonlocal collisionless power absorption in ICP discharges. 12 Theoretical and experimental results have shown that a proper application of weak external magnetic field to ICP discharges can improve many discharge parameters. However, the application of external magnetic field changes the electrodynamics of the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This model has been used recently to calculate the nonlocal collisionless power absorption in ICP discharges. 12 Theoretical and experimental results have shown that a proper application of weak external magnetic field to ICP discharges can improve many discharge parameters. However, the application of external magnetic field changes the electrodynamics of the plasma.…”
Section: Introductionmentioning
confidence: 99%